Evaluation of clopidogrel responsiveness using the Platelet Function Analyzer-200 (PFA-200) in dogs - Shin, Joon-Ho; Han, Hyun-Jung (Frontiers in Veterinary Science, 2025)
We aimed to evaluate the prevalence of clopidogrel resistance in hypercoagulable dogs using the Platelet Function Analyzer-200 (PFA-200) P2Y cartridge; further, we aimed to assess the utility of hematocrit (HCT), platelet count (PLT), prothrombin time (PT), activated partial thromboplastin time (aPTT), thromboelastography (TEG) parameters, and D-dimer level as indicators of clopidogrel efficacy. Forty healthy dogs underwent single measurements of P2Y closure time (CT), HCT, PLT, PT, aPTT, TEG parameters, and D-dimer levels, while thirty hypercoagulable dogs underwent two measurements of these parameters before and after clopidogrel treatment. The reference interval for P2Y CT in healthy dogs was 40.0–141.5 s, with a mean of 63.9 ± 26.82 s. Hypercoagulable dogs showed a mean baseline P2Y CT of 77.4 ± 37.6 s. Moreover, 23 (76.67%) and 7 (23.33%) showed responsiveness and resistance to the initial clopidogrel dose, respectively. The mean P2Y CT of the clopidogrel-resistant group after clopidogrel administration was 182.71 ± 78.43 s. Increasing the maintenance dose successfully overcame clopidogrel resistance in these seven dogs. Among the assessed parameters, only D-dimer levels showed a significant decrease in the clopidogrel-responder group (p < 0.05), suggesting its potential utility in evaluating responsiveness. In conclusion, the PFA-200 P2Y cartridge effectively detects clopidogrel resistance in dogs and can guide therapeutic adjustments such as dose escalation.